Effective demand for climate-smart adaptation: a case of solar technologies for cocoa irrigation in Ghana - Gbodji, Kekeli Kofi; Quarmine, William; Minh, Thai Thi (Informa UK Limited, 2023)
Given the generally low adoption of early climate change response technologies among tree crop producers in sub-Saharan Africa, stakeholders interested in the commercialization or scaling of such technologies will require empirical evidence of their market prospects. Using a double-bounded contingent valuation approach, the study evaluated the willingness and ability of 523 Ghanaian producers to invest in solar-powered irrigation pumps (SPIPs) for cocoa irrigation. The sample was split into three segments based on farm size: resource-poor, resource-limited, and resource-rich. Our results show that effective demand increased across the resource segments, with resource-endowed farmers more likely to demand SPIPs than resource-limited or resource-poor farmers. Also, while willingness to invest (WTI) depended on resourcefulness (land), farmers’ ability to invest was directly related to their resource (income class) endowment. We found that WTI across the resource segments was positively influenced by income, education, livestock ownership, credit, and extension services and negatively affected by household size and age of cocoa trees. Among others, we propose that promotional strategies for SPIPs should incorporate well-planned initiatives for income diversification and microcredit services to improve the financial position of the resource-poor and limited segment to encourage the adoption of these technologies.